2007
DOI: 10.1186/1471-2148-7-244
|View full text |Cite
|
Sign up to set email alerts
|

Complex phylogeographic history of central African forest elephants and its implications for taxonomy

Abstract: BackgroundPrevious phylogenetic analyses of African elephants have included limited numbers of forest elephant samples. A large-scale assessment of mitochondrial DNA diversity in forest elephant populations here reveals a more complex evolutionary history in African elephants as a whole than two-taxon models assume.ResultsWe analysed hypervariable region 1 of the mitochondrial control region for 71 new central African forest elephants and the mitochondrial cytochrome b gene from 28 new samples and compare thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(84 citation statements)
references
References 28 publications
9
73
2
Order By: Relevance
“…Our results are not unlike those of a recent study of North American captive savannah elephants that found no genetic structure in the founder population (Lei et al 2008) despite individuals having origins ranging from east, to central, to southern Africa (Olson 2003). Despite morphological Grubb et al 2000) and genetic (Roca et al 2001) differences between savannah and forest elephants being clear, introgression is evident in the wild populations (Roca et al 2004;Debruyne 2005;Johnson et al 2007), and admixture is shown in the captive population (see Debruyne 2005;Lei et al 2008). Analogous to the cryptic genetic variation and gene flow in elephants, our results show that there was genetic exchange between the two gorilla genetic clusters (as evidenced by the existence of admixed individuals in the wild-born founders) before they were moved from the wild in Africa to North America.…”
Section: Relatedness Genetic Variability and Inbreedingmentioning
confidence: 94%
“…Our results are not unlike those of a recent study of North American captive savannah elephants that found no genetic structure in the founder population (Lei et al 2008) despite individuals having origins ranging from east, to central, to southern Africa (Olson 2003). Despite morphological Grubb et al 2000) and genetic (Roca et al 2001) differences between savannah and forest elephants being clear, introgression is evident in the wild populations (Roca et al 2004;Debruyne 2005;Johnson et al 2007), and admixture is shown in the captive population (see Debruyne 2005;Lei et al 2008). Analogous to the cryptic genetic variation and gene flow in elephants, our results show that there was genetic exchange between the two gorilla genetic clusters (as evidenced by the existence of admixed individuals in the wild-born founders) before they were moved from the wild in Africa to North America.…”
Section: Relatedness Genetic Variability and Inbreedingmentioning
confidence: 94%
“…Background data on these vouchered samples were previously published [1]. While the forest elephant is recognized as a full species (Loxodonta cyclotis) by some researchers [20], here we follow CITES taxonomy and other researchers who treat Loxodonta from Africa as a single species (Loxodonta africana) [21].…”
Section: Methodsmentioning
confidence: 99%
“…As described above, problems related to sampling were well circumvented with animals. Indeed, by using shed hair or feces, which are non invasive methods of sampling, phylogenetic analyses have allowed a better understanding of the evolutionary history of gorillas [46] mandrills [47] or elephants [48]. Equally, a number of simian viruses have been characterized in fecal samples, which is more convenient, especially in case of wild-living primates.…”
Section: Opportunities and Challengesmentioning
confidence: 99%
“…Despite their morphology typical from forest elephants, a genetic study based on mtDNA [48] shows that Central African elephants are sharing their history with both forest and savannah elephants from Western Africa. It also gives evidence that Central African forest populations show lower genetic diversity than those in savannahs, and infers a recent population expansion.…”
Section: Central African Elephants: Forest or Savannah Elephants?mentioning
confidence: 99%